Cardiac tissue regeneration: A preliminary study on carbon‐based nanotubes gelatin scaffold. Issue 8 (5th December 2017) - Cabiati, Manuela; Vozzi, Federico; Gemma, Federica; Montemurro, Francesca; De Maria, Carmelo; Vozzi, Giovanni; Domenici, Claudio; Del Ry, Silvia
Abstract: The aim of this study was set‐up and test of gelatin and carbon nanotubes scaffolds. Gelatin‐based (5%) genipin cross‐linked (0.2%) scaffolds embedding single‐walled carbon nanotubes (SWCNTs, 0.3, 0.5, 0.7, 0.9, and 1.3% w/w) were prepared and mechanically/electrically characterized. For biological evaluation, H9c2 cell line was cultured for 10 days. Cytotoxicity, cell growth and differentiation, immunohistochemistry, and real‐time PCR analysis were performed. Myoblast and cardiac differentiation were obtained by serum reduction to 1% ( C 1% ) and stimulation with 50 nM all trans‐retinoic acid ( C RA ), respectively. Immunohistochemistry showed elongated myotubes in C 1% while round and multinucleated cells in C RA with also a significantly increased expression of natriuretic peptides (NP) and ET‐1 receptors in parallel with a decreased ET‐1. On scaffolds, cell viability was similar for Gel–SWCNT0.3%/0.9% ; NP and ET systems expression decreased in both concentrations with respect to control and CX‐43, mainly due to a lacking of complete differentiation in cardiac phenotype during that time. Although further analyses on novel biomaterials are necessary, these results represent a useful starting point to develop new biomaterial‐based scaffolds. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2750–2762, 2018.